The Effect of Self Regulation-Based Holistic Health Counseling Services in Improving Students' Psychological Well Being - Lucia Hernawati; Paraharesty Eriany (Universitas Katolik Soegijapranata, 2020)
The objective of this study was to determine the effect of self-regulation-based holistic health counseling in improving university students’ psychological wellbeing. Thirty students in Semarang who had low scores on Ryff's Psychological Wellbeing Scale participated as subjects in this study. An experiment was conducted with randomized pretest-post-test comparison group design for a total of 41 days. The experimental group was given a self-regulation-based holistic health counseling intervention. Meanwhile, students in the control group were given physical health interventions and effective study habits. Mann-Whitney U test was conducted to compare the effectiveness of the intervention in the experimental and control groups. The results of the research showed that compared to the control group, the intervention in the experimental group was more effective in increasing the students’ psychological wellbeing. The results of this study are useful as an alternative in helping students in Semarang to improve their psychological wellbeing.